The physiological relevance of downstream effectors of p53 activity - Vinod Pant; Sydney M. Moyer; Mitheera V; Amanda R. Wasylishen; Akshita Mirani; Natalie Fowlkes; Guillermina Lozano (Proceedings of the National Academy of Sciences, 2026)
The TP53 tumor suppressor encodes a transcription factor that regulates the expression of hundreds of target genes. Previous mouse studies have identified a conserved p53-dependent transcriptional signature that includes Cdkn1A (p21) , Gtse1 ( G2 and S-phase expressed 1 ), and Eda2r . In this study, we investigated the physiological roles of these three genes, along with Bbc3 (Puma), a p53 target involved in apoptosis, as effectors of p53 activity. We generated alleles of Gtse1 and Eda2r . In contrast to previously reported Cdkn1A-null and Bbc3-null mice which do not exhibit any overt phenotypes, mice expressing N-terminal deletions of Gtse1 ( Gtse1Δ7 ) and Eda2r ( Eda2rΔ11 ) displayed defects in spermatogenesis and liver abnormalities, respectively. We crossed these mice to an Mdm2 -deletion model that constitutively activates p53 resulting in multiple phenotypes and lethality. Notably, loss of p21 rescued the lethality associated with constitutive p53 activation in vivo, whereas the Gtse1Δ7 mutant partially rescued this effect; no rescue was observed with Eda2rΔ11 or Bbc3 loss. These findings indicate that cell cycle regulators, rather than apoptosis-related genes, are the main drivers of sustained p53-induced gastrointestinal defects and lethality.